Genome Sequence Resource of Phomopsis longicolla YC2-1, a Fungal Pathogen Causing Phomopsis Stem Blight in Soybean - Zhao, Xiaolin; Zhang, Zhichao; Zheng, Sujiao; Ye, Wenwu; Zheng, Xiaobo; Wang, Yuanchao (Molecular plant-microbe interactions, 2021)
Diaporthe-Phomopsis disease complex causes considerable yield losses in soybean production worldwide. As one of the major pathogens, Phomopsis longicolla T. W. Hobbs (syn. Diaporthe longicolla) is not only the primary agent of Phomopsis seed decay but is also one of the agents of Phomopsis pod and stem blight and Phomopsis stem canker. We performed both PacBio long-read sequencing and Illumina short-read sequencing and obtained a genome assembly for the strain P. longicolla YC2-1, which was isolated from soybean stem with Phomopsis stem blight disease. The 63.1 Mb genome assembly contains 87 scaffolds, with a minimum, maximum, and N 50 scaffold length of 20 kb, 4.6 Mb, and 1.5 Mb respectively, and a total of 17,407 protein-coding genes. The high-quality data expand the genomic resource of P. longicolla species and will provide a solid foundation for a better understanding of their genetic diversity and pathogenic mechanisms. [Formula: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license .